Extracellular vesicles concentration is a promising and important parameter for industrial bioprocess monitoring. Issue 5 (12th February 2016) - Zavec, Apolonija Bedina; Kralj‐Iglič, Veronika; Brinc, Matjaž; Trček, Tanja Ficko; Kuzman, Drago; Schweiger, Ana; Anderluh, Gregor
Abstract: Extracellular vesicles (EVs) are membrane vesicles that are produced by cells to be released into their microenvironment. In this study, we present the EV concentration as a new factor for optimization of industrial bioprocess control. The release of EVs depends on many cell properties, including cell activation and stress status, and cell death. Therefore, the EV concentration might provide a readout for identification of the cell state and the conditions during a bioprocess. Our data show that the EV concentration increased during the bioprocess, which indicated deteriorating conditions in the bioreactor. This increase in EV concentration in the fermentation broth was the consequence of two different processes: cell activation, and cell death. However, the release of EVs from activated living cells had a much weaker impact on EV concentration in the bioreactor than those released during cell death. EVs and cells in the bioprocess environment were quantified by flow cytometry. The most accurate data were obtained directly from unprocessed samples, making the monitoring of the EV concentration a rapid, easy, and cheap method. These EV concentrations reflect the conditions in the bioreactor and provide new information regarding the state of the bioprocess. Therefore, we suggest EV concentration as a new and important parameter for the monitoring of industrial bioprocesses. Abstract : The release of extracellular vesicles (EVs) depends on cell activation, cell stress, cell properties, and dying of cells; therefore, the authors have used the amount of released EVs for the identification of cell condition during the bioprocess. Their results have shown that EVs concentration reflects conditions in bioreactor and provide new information of the bioprocess state. EV concentration is suggested to be a new and important parameter for the monitoring of industrial bioprocesses.